Active Application of Database Technologies in Lexicographic Practice (Eurasian Journal of Learning and Academic Teaching, 2022)
The article is devoted to the problems of creating semantic fields when expressing the semantics of lexical units in a database format, a parametric description of the meaning of a word. Database technologies are actively used in lexicographic practice. In the field of creating lexicographic databases, including the semantic description of some semantic units, it will be necessary to develop a system for automatic translation of a natural language, a machine translation system